A Companion to African cinema - 4 0 16; 1968- Harrow, Kenneth W.,;Garritano, Carmela; 5 (Hoboken, NJ : Wiley Blackwell, 2019)
An authoritative guide to African cinema with contributions from a team of experts on the topic A Companion to African Cinema offers an overview of critical approaches to African cinema. With contributions from an international panel of experts, the Companion approaches the topic through the lens of cultural studies, contemporary transformations in the world order, the rise of globalization, film production, distribution, and exhibition. This volume represents a new approach to African cinema criticism that once stressed the sociological and sociopolitical aspects of a film. The text explores a wide range of broad topics including: cinematic economics, video movies, life in cinematic urban Africa, reframing human rights, as well as more targeted topics such as the linguistic domestication of Indian films in the Hausa language and the importance of female African filmmakers and their successes in overcoming limitations caused by gender inequality. The book also highlights a comparative perspective of African videoscapes of Southern Nigeria, Ethiopia, and COte d'Ivoire and explores the rise of Nairobi-based Female Filmmakers. This important resource: -Puts the focus on critical analyses that take into account manifestations of the political changes brought by neocolonialism and the waning of the cold war -Explores -Examines the urgent questions raised by commercial video about globalization -Addresses issues such as funding, the acquisition of adequate production technologies and apparatuses, and the development of adequately trained actors Written for film students and scholars, A Companion to African Cinema offers a look at new critical approaches to African cinema.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 15, 2018).
Keywords: 2 -- 0; 6; History and criticism. -- Motion pictures;Motion pictures. -- Africa; 20; Criticism, interpretation, etc.;Electronic books